Profile of Orthodontic Use across Demographics - Man Hung; Golnoush Zakeri; Sharon Su; Amir Mohajeri (MDPI AG, 2023)
Objectives: Population-based studies have focused on patients' rendering of orthodontic treatment due to their malocclusion and medical needs. However, there is a scarcity of data from national sources on the prevalence of orthodontic visits and associated patient characteristics, as well as their effect on dental health. This study evaluated the demographic differences of orthodontic patients and examined the association between orthodontics use and risk of periodontal disease and oral surgical intervention. Methods: This study used data collected from the 2019 Medical Expenditure Panel Survey. Descriptive statistics were used to evaluate socio-demographics and covariates by the use of orthodontics. Chi-square tests were used to assess demographic differences among respondents who stated whether or not they used orthodontics. Logistic regression models were then used to examine the association of orthodontics and oral health outcomes. Results: The sample size was 12,422, of which 491 respondents indicated a usage of orthodontics. There were significant differences among demographic variables (p < 0.05) that included 61.1% females, 60.8% Whites, 67.6% participants under the age of 18 years old, and a family total income of $100,000 or more (52.7%). After controlling for socio-demographics and covariates, individuals who used orthodontics were less likely to have periodontal disease (AOR = 0.623, 95% CI = 0.610 to 0.637) and tooth extractions (AOR = 0.071, 95% CI = 0.070 to 0.073) than those who did not. Conclusions: Our findings indicate orthodontics usage was higher in females, younger patients, and Whites, highlighting the possible demographic disparities in orthodontics use. Additionally, those who used orthodontics were less likely to have oral health issues.